Children’s Individual Differences in the Responses to a New Method for Physical Education - Sara Pereira; Carla Santos; José Maia; Olga Vasconcelos; Eduardo Guimarães; Rui Garganta; Cláudio Farias; Tiago V. Barreira; Go Tani; Peter T. Katzmarzyk; Fernando Garbeloto (Sports)
Children’s fundamental movement skills (FMS) require planned and guided interventions to develop appropriately. We investigated the effect of a novel Physical Education (PE) method to develop children’s object control, locomotor skills, and motor competence. Further, we examined children’s trainability, i.e., their differential responses to the new method, and identified low and high responders to the intervention. The study lasted three months and included six to seven-year-old children in two groups: control (the current, official PE program; n = 38) and experimental (the new method; n = 52). Twelve FMS [object control (OC), locomotor (LO)] were reliably assessed using the Meu Educativo® app. Using a mixed-effects model, results showed that the experimental group experienced greater changes (p < 0.05) than the control group in OC and LO. Positive individual changes were more frequent with the new method, but children showed a similar pattern in their interindividual variability in both methods. There was a greater reduction in the number of children with lower proficiency in the experimental group. In sum, the new PE method proved superior to the current, official one. Individual responses to the new method showed considerable variation, highlighting the need for personalization in teaching strategies and necessary support for children with lower proficiency levels, ensuring that no child is left behind in their motor development process.